Mass concrete and preparation method thereof
By using MXene composite phase change materials in large volume concrete, the temperature crack problem is solved, high stability and construction performance are improved, economic costs are reduced, and problems of low early strength and high construction difficulty in the existing technology are solved. .
Patent Information
- Application Number
- CN202411021764.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-29
AI Technical Summary
During the curing process of large-volume concrete, due to temperature cracks caused by uneven internal and external temperature distribution, the existing technical methods have problems such as low early strength, high construction difficulty, few applicable structural forms, and high economic costs.
Using MXene composite phase change material, a composite material with high thermal conductivity and phase change characteristics is prepared by mixing MXene nanosheets, lipophilic modified microcrystalline graphite, phase change aggregate, modified peanut shell powder and polyvinyl alcohol. , combined with low-alkali cement, fine aggregate, coarse aggregate and fly ash, the concrete formed reduces temperature difference in the hydration reaction and inhibits the formation of temperature cracks.
Effectively reduce the internal and external temperature difference caused by exothermic heat in hydration reaction, improve the stability and construction performance of the structure, high early strength and stable performance, significantly reduce the formation of temperature cracks, improve compressive, tensile strength and permeability resistance, Waterproofing capability.
Smart Images

Figure CN119118574A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete preparation, and in particular relates to a large volume concrete and a preparation method thereof. Background Art
[0002] As an indispensable and important engineering material in the field of construction, concrete is rich in resources, low in price, and easy to construct. It has been widely used in construction projects and bridge projects. However, due to the strong hydration reaction during its pouring process, the internal temperature rises too quickly, resulting in a significant increase in the temperature difference between the inside and the outside, thus forming temperature cracks, affecting the safety of the structure and shortening its service life. Compared with ordinary concrete, mass concrete has the characteristics of heavy structure, large volume, high technical requirements, and large hydration heat. There are certain differences in the definition of mass concrete in different countries. The current concrete construction specifications in the United States, Japan and my country have a vague definition of mass concrete, but all believe that when the size of concrete reaches a certain level, temperature control measures must be taken to inhibit the internal hydration reaction and prevent the temperature from rising too quickly, thereby preventing temperature cracks and ensuring structural safety. The foundation, abutment and main tower in bridge engineering are all mass concrete. Its specific characteristics are as follows: ① It is large in size and uses a large amount of various materials. For large bridge structures, the construction environment is complex, the technical requirements are high, and it is greatly affected by the external environment, so its temperature control is difficult; ② It has low tensile strength and is usually used together with steel bars to optimize its own bearing capacity through the excellent tensile properties of steel bars. However, since large-volume concrete has less reinforcement, it requires stronger tensile properties than ordinary reinforced concrete structures; ③ For large-volume concrete in bridge projects, it is not only necessary to have sufficient strength, rigidity, and stability, but also to have strong anti-seepage and waterproof capabilities. The piers and abutment structures of bridge projects are large-volume concrete structures. When the concrete is poured, the internal hydration reaction generates a large amount of heat. Due to the poor heat dissipation performance of the concrete material itself, the internal heat continues to accumulate and the temperature continues to rise. When the temperature reaches the peak, if necessary temperature control measures are not taken, a large temperature difference will form inside and outside the concrete. The initial concrete strength is low and the bearing performance is poor. It cannot withstand the thermal shrinkage stress. Once it exceeds the bearing range, cracks are bound to form. The continuous development of cracks will further form more harmful structural cracks, reduce the stability of the structure, and affect the safety and service life.
[0003] At present, the methods for controlling temperature cracks in large-volume concrete mainly include increasing the water-cement ratio of concrete, adding alkali-activated slag cementitious materials, layered pouring, and laying cooling pipes inside the concrete. These methods have problems such as low early strength, high construction difficulty, few applicable structural forms, and high economic cost. Based on the above analysis, it is very necessary to provide a large-volume concrete with a low degree of temperature cracks. Summary of the invention
[0004] The purpose of the present invention is to provide a large-volume concrete and a preparation method thereof in view of the above-mentioned deficiencies in the prior art, so as to solve the problem in the related art that large-volume precast concrete is prone to large-scale generation of temperature cracks due to uneven internal and external temperature distribution during the curing process.
[0005] To achieve the above object, the present invention adopts the following technical solution: The first object of the present invention is to provide a mass concrete, which is made of the following raw materials in parts by weight: 330-450 parts of cement, 430-510 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 3-10 parts of admixture, 3-9 parts of viscosity reducer, 50-100 parts of fly ash, and 5-15 parts of MXene composite phase change material. The MXene composite phase change material is prepared by the following method: spreading a mixture of MXene nanosheets, oleophilic modified microcrystalline graphite, phase change aggregate, modified peanut shell powder, and polyvinyl alcohol on a metal mold, then dropping a glutaraldehyde solution, stirring evenly, and heating to obtain a MXene composite phase change film; then chopping the MXene composite phase change film, and then covering the MXene composite phase change film fragments with polyvinyl alcohol by a suspension spray method, and drying to obtain a MXene composite phase change material.
[0006] Furthermore, the mass ratio of the MXene nanosheets, the oleophilic modified microcrystalline graphite, the phase change aggregate, the modified peanut shell powder, and the polyvinyl alcohol solution is 1: (0.02-0.05): (0.2-0.4): (0.05-0.1): (0.3-0.5).
[0007] Furthermore, the particle size of MXene nanosheets ranges from 200 to 800 nm.
[0008] Furthermore, the MXene composite phase change film is chopped into pieces with a particle size of 0.5 to 2 mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method and dried to obtain a MXene composite phase change film.
[0009] Furthermore, the preparation process of the oleophilic modified microcrystalline graphite is as follows: 0.5-1 parts of stearic acid are dissolved in a solvent consisting of 250 parts of deionized water and 50 parts of anhydrous ethanol, and then 10 parts of microcrystalline graphite and 0.55 parts of aluminum chloride hexahydrate are added as a catalyst to obtain a first suspension; then the water bath temperature is increased to 70-80°C, the stirring rate is 200-300 r / min, stirring is performed for 2-2.5 hours, washing and drying are performed to obtain the oleophilic modified microcrystalline graphite.
[0010] Furthermore, the preparation process of the phase change micro-aggregate is as follows: 0.5-1 parts of disodium hydrogen phosphate dodecahydrate and 1 part of sodium sulfate dihydrate are uniformly mixed to obtain a phase change core material, and 0.1-0.2 parts of glycerol are added to inhibit the phase separation of the phase change material; after mixing 1 part of the phase change core material with 0.5 parts of expanded perlite, the phase change core material is heated to completely melt; then, negative pressure is applied to allow the phase change core material to be absorbed into the expanded perlite to obtain a phase change aggregate.
[0011] Furthermore, the cement is P.O42.5 low-alkali cement; and the viscosity reducer is K-335.
[0012] Furthermore, the fine aggregate is natural river sand, with a mud content of 0.9% and a fineness modulus of 2.6-2.8; the coarse aggregate is continuously graded basalt crushed stone with a particle size of 5-20 mm and an apparent density of 2740-2900 kg / m 3 , the crushing value is 7~9%.
[0013] Furthermore, the fly ash is Class F, Grade I fly ash, with a loss on ignition of 1.5-3.5% and a water requirement ratio of 90-95%.
[0014] The second object of the present invention is to provide a method for preparing the above-mentioned mass concrete, wherein cement, fine aggregate, coarse aggregate, fly ash, viscosity reducer and MXene composite phase change material are evenly mixed, water and admixtures are added, mixed, stirred and cured to obtain mass concrete with low temperature cracking degree.
[0015] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: (1) The mass concrete prepared in this application effectively reduces the internal and external temperature difference and temperature peak caused by the heat release of hydration reaction before and during the curing period of the mass concrete by introducing MXene composite phase change materials, thereby inhibiting the generation of temperature cracks. In addition, the concrete effectively reduces the temperature stress caused by uneven temperature distribution in a large temperature difference environment and improves the volume stability of the structure. The concrete has excellent working performance, weather resistance and construction performance, high early strength and stable performance.
[0016] (2) In the present application, concentrated hydrochloric acid and hydrogen fluoride are used as etching solutions to treat titanium aluminum carbide, which effectively increases the specific surface area of titanium aluminum carbide, improves the compatibility of titanium aluminum carbide with polyvinyl alcohol, makes it more evenly distributed, and improves the stability and safety of the MXene composite phase change material; at the same time, titanium aluminum carbide has high thermal conductivity, which improves the sensitivity and responsiveness of the phase change material to changes in concrete temperature.
[0017] (3) This application introduces oleophilic modified microcrystalline graphite to improve the compatibility of graphite and polyvinyl alcohol, which can greatly improve the uniformity of graphite distribution. Microcrystalline graphite has excellent thermal conductivity, which significantly improves the thermal sensitivity of MXene composite phase change materials and increases the response speed and accuracy of concrete temperature control.
[0018] (4) The present application uses expanded perlite as porous aggregate and uses disodium hydrogen phosphate dodecahydrate and sodium sulfate dihydrate to form a high thermal conductivity phase change core material, which has the characteristics of low raw material cost, easy batch production, and low risk of phase change core material leakage. The phase change core material has high temperature sensing sensitivity and a wide sensing temperature range, and the temperature regulation inside the concrete is more stable and controllable.
[0019] (5) This application introduces organic long fibers into large-volume concrete by adding modified peanut shell powder, which effectively enhances the toughness of large-volume concrete and significantly improves the compressive and tensile strengths of concrete. The modified peanut shell powder has good compatibility with the MXene composite phase change material carrier and cement slurry, and the dosage can be adjusted freely within a wide range according to needs. It is environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a transmission electron microscope image of Mxene nanosheets. It is observed that the particle size of the prepared nanosheets is 200~800nm and is a single-layer structure. Figure 2 and Figure 3 They are scanning electron microscope images of Mxene composites, and it is observed that the Mxene composites are multi-layered structures with a large number of phase change aggregates embedded in the layered structures; Figure 4 This is the differential scanning calorimetry analysis diagram of the Mxene composite material. The phase transition temperature of the Mxene composite material is 49.1℃, and the phase transition latent heat is 89.5 J / g; Figure 5 This is a photo of the concrete surface cracks prepared in Example 6; Figure 6 This is a photo of the concrete surface cracks prepared in Comparative Example 1. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0022] The mass concrete provided in the embodiment of the present application includes 330-450 kg / m of cement by weight.3 , fine aggregate 430~510kg / m 3 , coarse aggregate 1000~1200kg / m 3 , admixture 3~10kg / m 3 , fly ash 50~100kg / m 3 MXene composite phase change material 5~15kg / m 3 ; The MXene composite phase change material includes MXene nanosheets, phase change aggregate, oleophilic modified microcrystalline graphite, modified peanut shell powder, and polyvinyl alcohol; the phase change aggregate includes a phase change core composed of disodium hydrogen phosphate dodecahydrate and sodium sulfate dihydrate, and expanded perlite (as a porous aggregate); the cement is P.042.5 low-alkali cement; the viscosity ratio of the viscosity reducer K-335 is 23, the fluidity ratio is 112, and the 28d compressive strength ratio is 92; the fine aggregate is natural river sand with a mud content of 0.9% and a fineness modulus of 2.6~2.8; the coarse aggregate is a continuously graded basalt crushed stone with a particle size of 5~20mm and an apparent density of 2740~2900kg / m 3 , the crushing value is 7~9%; the fly ash is Class F Grade I fly ash, the loss on ignition is 1.5~3.5%, and the water requirement ratio is 90~95%.
[0023] Adding viscosity reducers can reduce the plastic viscosity of concrete and effectively improve the working performance and pumping performance of concrete.
[0024] MXene nanosheets are made through the following process: 500 mL of concentrated hydrochloric acid and 500 mL of hydrogen fluoride were mixed at a molar ratio of 1:1 to prepare an etching solution. The titanium aluminum carbide was dried at 30°C. 10 g of the dried titanium aluminum carbide was added to the etching solution (molar ratio 1:1), and stirred at 200 rpm for 1.5 hours to obtain a titanium aluminum carbide suspension. The etched titanium aluminum carbide was washed 5 times, and then the suspension was centrifuged and freeze-dried to obtain MXene nanosheets. Figure 1 As shown, it is a transmission electron microscope image of Mxene nanosheets; it is observed that the particle size of the prepared nanosheets is 200~800nm and has a single-layer structure.
[0025] Modified peanut shell powder is prepared by the following process: The peanut shells were dried and crushed to less than 300 meshes. 1L of a 0.1% HCl solution was prepared with deionized water and concentrated hydrochloric acid. The peanut shell powder was put into the 0.1% HCl solution for acid washing for 12 hours, then ammonia water was added to neutralize it to neutrality, and the modified peanut shell powder was obtained by drying.
[0026] Oleophilic modified microcrystalline graphite is prepared by the following process: 0.7 g of stearic acid was dissolved in a solvent consisting of 250 mL of deionized water and 50 mL of anhydrous ethanol, and then 10 g of microcrystalline graphite and 0.55 g of aluminum chloride hexahydrate were added as a catalyst to obtain a first suspension; then the water bath temperature was increased to 73°C, the stirring rate was 300 r / min, stirred for 2 h, washed and dried to obtain lipophilic modified microcrystalline graphite.
[0027] Phase change aggregate is produced by the following process: 0.8 g of disodium hydrogen phosphate dodecahydrate and 1 g of sodium sulfate dihydrate were uniformly mixed, and 0.1-0.2 mL of glycerol was added to obtain a phase change core material. 1 part of the phase change core material was mixed with 0.5 g of expanded perlite, and then placed in a 70°C water bath environment to completely melt the phase change core material. Then, negative pressure was applied to allow the phase change core material to be absorbed into the expanded perlite to obtain a phase change aggregate.
[0028] MXene composite phase change materials are prepared through the following process: 1g MXene nanosheets, 0.05g oleophilic modified microcrystalline graphite, 0.3g phase change aggregate, 0.1g modified peanut shell powder, 0.4g polyvinyl alcohol solution mixture was spread on a metal mold, and then 2% glutaraldehyde solution of polyvinyl alcohol was added dropwise, stirred evenly, heated to 70°C, and continued for 2h to obtain a preliminary MXene composite phase change film; the above MXene composite phase change film was chopped into pieces with a particle size of 0.8mm, and then polyvinyl alcohol was covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material. Figure 2 and Figure 3 As shown in the figure, they are scanning electron microscope images of Mxene composite materials. It is observed that the Mxene composite material is a multilayer structure, and a large number of phase change aggregates are embedded in the layered structure; Figure 4 The figure shows the differential scanning calorimetry analysis diagram of the Mxene composite material. The phase transition temperature of the Mxene composite material is 49.1°C and the latent heat of the phase change is 89.5 J / g.
[0029] Description of the raw materials used in the embodiments of the present invention: Viscosity reducer K-335: purchased from Xinda Henglian (Beijing) Engineering Materials Technology Co., Ltd.; Admixture: polycarboxylic acid water reducer, purchased from Jiangsu Subote Co., Ltd., with a water reduction rate of 28%; Example 1 This embodiment 1 provides a method for preparing a large volume of concrete, comprising the following steps: Step S101, by weight, 1g of MXene nanosheets, 0.04g of oleophilic modified microcrystalline graphite, 0.35g of phase change aggregate, 0.075g of modified peanut shell powder, and 0.4mL of polyvinyl alcohol solution are spread evenly on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2.5 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.5-1.5mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 380 kg / m 3 Cement, 470kg / m 3 Fine aggregate, 1100kg / m 3 Coarse aggregate, 7kg / m 3 Viscosity reducer K-335, 80kg / m 3 Fly ash, 5kg / m 3 After the MXene composite phase change material is mixed evenly, add 210kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete.
[0030] In Example 1, the fine aggregate is river sand with a fineness modulus of 2.6 and a mud content of 0.9%; the coarse aggregate is 5-20 mm continuously graded granite crushed stone with an apparent density of 2740 kg / m 3 , the crushing value is 8%.
[0031] Example 2 This embodiment provides a method for preparing a large volume of concrete, comprising the following steps: Step S101, by weight, 1g of MXene nanosheets, 0.02g of oleophilic modified microcrystalline graphite, 0.2g of phase change aggregate, 0.05g of modified peanut shell powder, and 0.3mL of polyvinyl alcohol solution are spread evenly on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.1-2mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 330 kg / m 3 Cement, 430kg / m 3 Fine aggregate, 1000kg / m 3 Coarse aggregate, 3kg / m 3 Viscosity reducer K-335, 50kg / m3 Fly ash, 5.8kg / m 3 After the MXene composite phase change material is mixed evenly, 170 kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete.
[0032] In Example 2, the fine aggregate is river sand with a fineness modulus of 2.8 and a mud content of 0.9%; the coarse aggregate is 10-20 mm continuously graded granite crushed stone with an apparent density of 2740 kg / m 3 , the crushing value is 7%.
[0033] Example 3 This embodiment provides a method for preparing a large volume of concrete, comprising the following steps: Step S101, by weight, 1g of MXene nanosheets, 0.04g of oleophilic modified microcrystalline graphite, 0.25g of phase change aggregate, 0.08g of modified peanut shell powder, and 0.35mL of polyvinyl alcohol solution are spread evenly on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.5-2mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 330 kg / m 3 Cement, 460kg / m 3 Fine aggregate, 1050kg / m 3 Coarse aggregate, 4.7kg / m 3 Viscosity reducer K-335, 68kg / m 3 Fly ash, 7.3kg / m 3 After the MXene composite phase change material is mixed evenly, 195 kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete.
[0034] In Example 3, the fine aggregate is river sand with a fineness modulus of 2.8 and a mud content of 0.8%; the coarse aggregate is 5-10 mm continuously graded granite crushed stone with an apparent density of 2850 kg / m 3 , the crushing value is 9%.
[0035] Example 4 This embodiment provides a method for preparing a large volume of concrete, comprising the following steps: Step S101, by weight, 1g of MXene nanosheets, 0.03g of oleophilic modified microcrystalline graphite, 0.36g of phase change aggregate, 0.077g of modified peanut shell powder, and 0.45mL of polyvinyl alcohol solution mixture are spread on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.7 to 1.8 mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 420 kg / m 3 Cement, 500kg / m 3 Fine aggregate, 1160kg / m 3 Coarse aggregate, 6.5kg / m 3 Viscosity reducer K-335, 85kg / m 3 Fly ash, 9.5kg / m 3 After the MXene composite phase change material is mixed evenly, 188 kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete.
[0036] In Example 4, the fine aggregate is river sand with a fineness modulus of 2.6 and a mud content of 1.2%; the coarse aggregate is 5-20 mm continuously graded granite crushed stone with an apparent density of 2810 kg / m 3 , the crushing value is 7%.
[0037] Example 5 Example 5 of the present application provides a method for preparing a large volume concrete with a low temperature crack degree, comprising the following steps: Step S101, by weight, 1g of MXene nanosheets, 0.04g of oleophilic modified microcrystalline graphite, 0.31g of phase change aggregate, 0.1g of modified peanut shell powder, and 0.5mL of polyvinyl alcohol solution are spread evenly on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.5 to 2mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 360 kg / m 3 Cement, 488kg / m 3 Fine aggregate, 1190kg / m 3 Coarse aggregate, 9kg / m 3Viscosity reducer K-335, 82kg / m 3 Fly ash, 9.8kg / m 3 After the MXene composite phase change material is mixed evenly, 174 kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete.
[0038] In Example 5, the fine aggregate is river sand with a fineness modulus of 2.8 and a mud content of 0.9%; the coarse aggregate is 5-18 mm continuously graded granite crushed stone with an apparent density of 2900 kg / m 3 , the crushing value is 8%.
[0039] Example 6 This embodiment provides a method for preparing a large volume of concrete, comprising the following steps: Step S101, by mass, 1g of MXene nanosheets, 0.022g of oleophilic modified microcrystalline graphite, 0.34g of phase change aggregate, 0.058g of modified peanut shell powder, and 0.41mL of polyvinyl alcohol solution mixture are spread on a metal mold, and then a glutaraldehyde solution accounting for 2% of the mass fraction of polyvinyl alcohol is added dropwise, stirred evenly, and heated to 70°C for 2 hours to preliminarily obtain a MXene composite phase change film; the above MXene composite phase change film is chopped into pieces with a particle size of 0.5-2mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method, and dried to obtain a MXene composite phase change material; Step S102, by mass, 368 kg / m 3 Cement, 495kg / m 3 Fine aggregate, 1156kg / m 3 Coarse aggregate, 7kg / m 3 Viscosity reducer K-335, 65kg / m 3 Fly ash, 14.5kg / m 3 After the MXene composite phase change material is mixed evenly, add 200kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete. Figure 5 shown.
[0040] In Example 6, the fine aggregate is river sand with a fineness modulus of 2.8 and a mud content of 0.8%; the coarse aggregate is 5-20 mm continuously graded granite crushed stone with an apparent density of 2870 kg / m 3 , the crushing value is 7%.
[0041] Comparative Example 1 By mass, 440kg / m 3 Cement, 480kg / m 3Fine aggregate, 1200kg / m 3 Coarse aggregate, 9kg / m 3 Viscosity reducer, 86kg / m 3 Fly ash, 4kg / m 3 Phase change aggregate, 0.8g / m 3 Modified peanut shell powder, 10kg / m 3 After the MXene nanosheets are mixed evenly, 200 kg / m 3 Water and admixtures are mixed and stirred to produce mass concrete. Figure 6 shown.
[0042] In Comparative Example 1, the fine aggregate is river sand with a fineness modulus of 2.6 and a mud content of 1.1%; the coarse aggregate is 5-20 mm continuously graded granite crushed stone with an apparent density of 2760 kg / m 3 , the crushing value is 9%.
[0043] With reference to the requirements of GBT 50081-2019, the mechanical properties of the concrete prepared in Example 1, Example 6 and Comparative Example 1 were tested, and the results are shown in Table 1. With reference to the requirements of GB / T 50080-2016, the adiabatic temperature rise value of the concrete prepared in Example 1, Example 6 and Comparative Example 1 was tested using a concrete adiabatic temperature rise meter, and the results are shown in Table 2.
[0044] Table 1: Test results of working performance and mechanical properties of concrete obtained from Examples 1 to 5 and Comparative Example 1
[0045] Table 2: Test results of concrete insulation temperature rise test
[0046] It can be seen from Table 1 that within a certain range, adding more MXene composite phase change materials is beneficial to reducing the scale of temperature cracks, which is reflected in the gradual reduction in the width of the cracks on the concrete surface. Compared with the comparative example, the maximum width of the surface cracks in Example 6 was reduced by 55.2%.
[0047] It can be seen from Table 2 that with the increase in the amount of MXene composite phase change material, the adiabatic temperature rise value of each embodiment group at 7d gradually decreases, which is attributed to the solid-liquid phase change of the phase change material, which absorbs part of the heat released during the cement hydration process.
[0048] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A mass concrete, characterized in that: The invention is prepared from the following raw materials in parts by weight: 330-450 parts of cement, 430-510 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 3-10 parts of admixture, 3-9 parts of viscosity reducer, 50-100 parts of fly ash and 5-15 parts of MXene composite phase change material. The MXene composite phase change material is prepared by the following method: spreading a mixture of MXene nanosheets, oleophilic modified microcrystalline graphite, phase change aggregate, modified peanut shell powder and polyvinyl alcohol on a metal mold, then dropping a glutaraldehyde solution, stirring evenly and heating to obtain a MXene composite phase change film; then chopping the MXene composite phase change film, and then covering the MXene composite phase change film fragments with polyvinyl alcohol by a suspension spray method, and drying to obtain a MXene composite phase change material.
2. The mass concrete according to claim 1, characterized in that: The mass ratio of the MXene nanosheets, oleophilic modified microcrystalline graphite, phase change aggregate, modified peanut shell powder, and polyvinyl alcohol solution is 1: (0.02-0.05): (0.2-0.4): (0.05-0.1): (0.3-0.5).
3. The mass concrete according to claim 2, characterized in that: The particle size of MXene nanosheets ranges from 200 to 800 nm.
4. The mass concrete according to claim 3, characterized in that: The MXene composite phase change film is cut into pieces with a particle size of 0.5-2 mm, and then polyvinyl alcohol is covered on the MXene composite phase change film fragments by a suspension spray method and dried to obtain a MXene composite phase change film.
5. The mass concrete according to claim 4, characterized in that: The preparation process of the oleophilic modified microcrystalline graphite is as follows: 0.5-1 parts of stearic acid are dissolved in a solvent composed of 250 parts of deionized water and 50 parts of anhydrous ethanol, and then 10 parts of microcrystalline graphite and 0.55 parts of aluminum chloride hexahydrate are added as a catalyst to obtain a first suspension; then the water bath temperature is increased to 70-80°C, the stirring rate is 200-300 r / min, stirring is performed for 2-2.5 hours, washing and drying are performed to obtain the oleophilic modified microcrystalline graphite.
6. The mass concrete according to claim 5, characterized in that: The preparation process of the phase change micro-aggregate is as follows: 0.5-1 parts of disodium hydrogen phosphate dodecahydrate and 1 part of sodium sulfate dihydrate are uniformly mixed to obtain a phase change core material, and 0.1-0.2 parts of glycerol are added to inhibit the phase separation of the phase change material; 1 part of the phase change core material is mixed with 0.5 parts of expanded perlite, and then heated to completely melt the phase change core material; then, negative pressure is drawn to allow the phase change core material to be absorbed into the expanded perlite to obtain the phase change aggregate.
7. The mass concrete according to claim 1, characterized in that: The cement is P.O42.5 low-alkali cement; the viscosity reducer is K-335.
8. The mass concrete according to claim 1, characterized in that: The fine aggregate is natural river sand with a mud content of 0.9% and a fineness modulus of 2.6-2.8; the coarse aggregate is basalt crushed stone with a particle size of 5-20 mm and a surface density of 2740-2900 kg / m 3 , the crushing value is 7~9%.
9. The mass concrete according to claim 1, characterized in that: The fly ash is Class F, Grade I fly ash, with a loss on ignition of 1.5-3.5% and a water requirement ratio of 90-95%.
10. A method for preparing mass concrete according to any one of claims 1 to 9, characterized in that: After cement, fine aggregate, coarse aggregate, fly ash, viscosity reducer and MXene composite phase change material are evenly mixed, water and admixtures are added, mixed, stirred and cured to obtain large-volume concrete with low temperature cracking degree.
Citation Information
Patent Citations
C50 phase change energy storage concrete with high-titanium slag as phase change carrier and preparation method thereof
CN109485347A
MXene composite phase change microcapsule and preparation method thereof
CN112892428A
Light and heat storage type composite phase change material for energy storage and preparation method of light and heat storage type composite phase change material
CN113136172A
Novel thermal insulation mortar and preparation method thereof
CN115196912A
